Efficient reduction of 4-nitrophenol catalyzed by 4-carbo-methoxypyrrolidone modified PAMAM dendrimer–silver nanocomposites. Issue 21 (11th October 2019) - Yang, Desheng; Zhang, Rui; Zhao, Ting; Sun, Tingting; Chu, Xiaomeng; Liu, Shaojie; Tang, Erjun; Xu, Xiaodong
Abstract : Ag–PPDNCs prepared with 4-carbomethoxypyrrolidone modified PAMAM showed very high activity in the reduction of 4-nitrophenol. Abstract : Due to their small size, uniform dispersion and good stability, dendrimer encapsulated nanoparticles (DENs) are widely used as nanocomposite materials. However, as a commonly used template, the polyamidoamine (PAMAM) dendrimer is limited in the biological and medical fields because of its toxicity. Besides, nanoparticles are commonly encapsulated inside dendrimers, which limits their effective contact with the reactants. In this paper, we presented a comprehensive investigation on the synthesis, characterization and application of 4-carbomethoxypyrrolidone modified polyamidoamine (PAMAM-Pyr) dendrimer–silver nanocomposites (Ag–PPDNCs). The silver nanoparticles were stabilized by PAMAM-Pyr, which combined the advantages of PAMAM and polyvinylpyrrolidone (PVP). Compared with particles prepared with PVP or PAMAM, silver nanoparticles prepared with PAMAM-Pyr had smaller particle sizes with a narrow distribution of 4.78 ± 0.57 nm, which were a kind of mixed type of dendrimer nanocomposite. In addition, Ag–PPDNCs showed a very high activity in the reduction of 4-nitrophenol with an observed rate constant of up to 7.2 × 10 −3 s −1 and the turnover frequency was as high as 948.6 h −1, which was superior to that of other reported templates. These results demonstrated the significant role of PAMAM-Pyr in the preparation of Ag–PPDNCs with small particle sizes and excellent catalytic reduction properties. Due to its excellent application performance and low toxicity, PAMAM-Pyr has great application potential in the fields of catalysis and medicine.